2014
DOI: 10.1007/s00705-014-2276-z
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic reorganization of the family Bornaviridae

Abstract: Knowledge of bornaviruses has expanded considerably during the last decade. A possible reservoir of mammalian Borna disease virus has been identified, divergent bornaviruses have been detected in birds and reptiles, and endogenous bornavirus-like elements have been discovered in the genomes of vertebrates of several species. Previous sequence comparisons and alignments have indicated that the members of the current family Bornaviridae are phylogenetically diverse and are not adequately classified in the existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
94
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 54 publications
0
94
0
6
Order By: Relevance
“…Bornaviruses (Order Mononegavirales Family Bornaviridae) are phylogenetically diverse, nonsegmented, negative single-stranded RNA viruses [1][2][3]. Borna disease virus 1 (BoDV-1), as part of the species Mammalian 1 bornavirus, is a highly neurotropic prototype of Bornaviruses and infects a wide variety of mammal species [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Bornaviruses (Order Mononegavirales Family Bornaviridae) are phylogenetically diverse, nonsegmented, negative single-stranded RNA viruses [1][2][3]. Borna disease virus 1 (BoDV-1), as part of the species Mammalian 1 bornavirus, is a highly neurotropic prototype of Bornaviruses and infects a wide variety of mammal species [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…To date, 15 avian bornaviruses have been identified in a broad range of avian hosts, including Psittaciformes, Passeriformes and waterfowl (Afonso et al, 2016;Kuhn et al, 2015;Philadelpho et al, 2014). Parrot bornaviruses 2 (PaBV-2) and 4 (PaBV-4) are widely distributed in captive psittacine populations (Heffels-Redmann et al, 2011;Rubbenstroth et al, 2012) and were demonstrated to be the causative agents of proventricular dilatation disease (PDD) in these birds (Gray et al, 2010;Mirhosseini et al, 2011;Piepenbring et al, 2012;Rubbenstroth et al, 2014).…”
mentioning
confidence: 99%
“…Bornaviruses are slowly replicating viruses that can persistently infect neurons and various other cell types in susceptible hosts. Disease is assumed to result from virus-induced immunopathology rather than from direct cell damage (reviewed in Kuhn et al, 2015;Staeheli et al, 2010). PDD in psittacines is a mostly chronic and often fatal disease, which is characterized by gastrointestinal or neurological signs or a combination of both.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Delnatte et al (2011) examined fixed tissues from birds with neurologic disease and detected bornavirus sequences in brain tissue from wild Canada Geese (Branta canadensis) and Trumpeter Swans (Cygnus buccinator) in eastern Canada. This virus has been named aquatic bird bornavirus 1 (ABBV-1; Kuhn et al 2014). ABBV-1 infection is common and widespread across the US in several species of wild geese including Canada Geese, Snow Geese (Chen caerulensis), and Ross's Geese (Chen rossii) as well as in Mute Swans (Cygnus olor).…”
mentioning
confidence: 99%